The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/are.14616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of malic acid and citric acid on growth performance, antioxidant capacity, haematology and immune response of Carassius auratus gibelio

Abstract: The aim of this study was to investigate the effects of citric acid (CA) and malic acid (MA) on growth performance, antioxidant capacity, haematology and immune response of Carassius auratus gibelio. Carassius auratus gibelio were randomly divided into six groups, with three replicates in each group and 20 fish in each replicate.The six groups were fed a basic diet with organic acid supplementation (control group, 0.2%MA, 0.2%MA + 0.1%CA, 0.2%MA + 0.2%CA, 0.2%MA + 0.4%CA and 0.2%MA + 0.6%CA) for 8 weeks respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…An exception to this is seen in malic acid, which showed a very strong (R = 0.7–1.0) and significant correlation against antioxidant potential determined by the ABTS and DPPH methods (R = 0.878 and 0.824, respectively) and a strong correlation (R = 0.5–0.7) against activity determined by the FRAP method, only (R = 0.652). The antioxidant activity of malic acid was confirmed previously [ 55 ]. Malic acid is considered as safe when it is at low concentrations.…”
Section: Resultssupporting
confidence: 67%
“…An exception to this is seen in malic acid, which showed a very strong (R = 0.7–1.0) and significant correlation against antioxidant potential determined by the ABTS and DPPH methods (R = 0.878 and 0.824, respectively) and a strong correlation (R = 0.5–0.7) against activity determined by the FRAP method, only (R = 0.652). The antioxidant activity of malic acid was confirmed previously [ 55 ]. Malic acid is considered as safe when it is at low concentrations.…”
Section: Resultssupporting
confidence: 67%
“…In addition, the GC/MS analysis suggested that the putative anti-proliferative molecule in the aqueous phase of OsCFS might be malic acid. Malic acid is an organic compound that has been reported to have many bioactive functions, such as antioxidant activity, capturing free radicals, and antimicrobial activity against some pathogenic bacteria ( Eswaranandam et al, 2006 ; Zhang et al, 2020 ). In addition, malic acid can be chemically polymerized to polymalic acid, which has a wide range of applications in cancer therapy because of its biochemical properties, including its biocompatibility, biodegradability, and chemical modifiability ( Zeng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that acidifiers can accelerate growth indices and FI via influencing the parasympathetic nervous system on the appetite-related gene (GHR; Hoseinifar, Sun, et al, 2017;Zhang et al, 2020). GHR is a multifunctional hormone that is involved in inducing growth hormone and insulin release, blood glucose control, gastric acid secretion and appetite (Kojima & Kangawa, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In this vein, organic acids or acidifiers (salts of organic acids) are one of the functional additives with innumerable beneficial effects in aquaculture nutrition. Earlier reports have confirmed that diets supplemented with acidifiers can support fish health by enhancing immune responses in the serum and mucus of the fish (Mohammadian et al, 2020;Sotoudeh et al, 2020;Zhang et al, 2020). Other findings have shown that adding acidifiers to the fish diet can act as a growth enhancer by increasing the rate of protein digestibility, nutrient absorption and mineral retention and upregulating the expression of growth-related genes (Kalantarian et al, 2020;Mohammadian et al, 2020;Ng & Koh, 2017;Zhou et al, 2009).…”
Section: Introductionmentioning
confidence: 91%